SOCIAL CRITICISM IN THE MISTER FRIMEN ANIMATED SERIES - Ristiasari, Riska; Kaprisma, Hendra (Capture : Jurnal Seni Media Rekam, 2021)
Social criticism is generally comprised of individuals' ideas and opinions of societal problems that bring changes. Individuals can express their opinions through various media, including animated films. The animated series Mister Frimen created by Pavel Muntyan, Vladimir Ponomarev, Anatoly Dobrozan, and Vadim Demchog are notoriously sarcastic. The sarcastic remarks given by the main character are always about current problems in Russian society. This study focuses on the way the animated series Mister Frimen expresses social problems. This article uses intertextual theory and discourse analysis to analyze every message and symbol and how the messages are generated. The results show that each scene in Mister Frimen contains symbols illustrating social criticism messages about the situation of Russian society. Nonetheless, satire/social criticism offers suggestions for establishing societal peace and prosperity